The Influence of Maslahah, Cultural, Social, Personal, and Psychological Factors on Generation Z’s Decision to Purchase Secondhand Clothing - Ela Inayatul Lutfiyah; Rachma Indrarini (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
This study aims to analyze the influence of maslahah, cultural, social, personal, and psychological factors on the purchase decision of secondhand clothes in Generation Z in Surabaya. This study uses a quantitative method with an associative approach. The sample was taken using purposive sampling techniques from Generation Z respondents in the city of Surabaya who had purchased secondhand clothes. Primary data were collected through questionnaires and analyzed using Partial Least Square-Structural Equation Modelling (PLS-SEM). The results of the study show that maslahah and cultural factors have no influence on the purchase decision. These findings indicate that consideration of benefits and cultural values are not the main determinants in secondhand clothing purchase decisions in Generation Z. On the contrary, other factors such as social, personal, and psychological show a significant positive influence on purchase decisions. This shows that the influence of the social environment, individual characteristics, and psychological aspects such as motivation and perception have a dominant role in shaping secondhand clothing purchase decisions in Generation Z